IMPLEMENTASI MODEL PERMAINAN BOLAVOLI TERHADAP PENINGKATAN MOTIVASI PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN MURID SEKOLAH DASAR NEGERI 07 MAGEK KABUPATEN AGAM - Luisa Pernanda, Tiara; Yuni Astuti, Yuni Astuti; Berto Apriyano, Berto Apriyano; Haripah Lawanis4, Haripah Lawanis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low learning motivation of students in participating in Physical Education, Sports, and Health (PJOK) learning at State Elementary School 07 Magek, Agam Regency. This study aims to improve student learning motivation through the implementation of the volleyball game model in PJOK learning at State Elementary School 07 Magek, Agam Regency. This type of research is Classroom Action Research (CAR). The subjects of the study were 16 fourth grade students. Data collection techniques used in this study were questionnaires, observation sheets, and documentation. Data analysis techniques used quantitative descriptive analysis. The results of the study concluded that the implementation of the volleyball game model can improve student learning motivation in PJOK learning. At the pre-cycle stage, student learning motivation was in the low category for 3 students (18.75%), the medium category for 10 students (62.50%), the high category for 2 students (12.50%), and the very high category for 1 student (6.25%). After the action was given, the observation results of learning motivation in Cycle I reached 70.31% with a good category, then increased in Cycle II to 96.88% with a very good category. The results of the questionnaire in Cycle II showed that as many as 5 students (31.25%) were in the high category and 11 students (68.75%) were in the very high category, with a percentage of learning motivation of 92.50% which was included in the very high category.